Available space in feeders for housed sheep: social behavior and performance - Andrade da Silveira, Jose Coriolano; Carvalho Fonseca, Vinicius de Franca [UNESP]; Furtado, Dermeval Araujo; Caetano Goncalves dos Santos, Severino Guilherme; Silva, Josinaldo Araujo da; Pimenta Filho, Edgard Cavalcanti; Saraiva, Edilson Paes; Medeiros, Ariosvaldo Nunes de (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
This study was designed to assess the effects of feeding space availability on social behavior and performance of housed crossbreed sheep through the use of three different types of feeders. Thirty-six crossbreed ewes (Santa Ines x Dorper; 2-3 years old) with initial body weight of 34.99 +/- 4.28 kg were randomly assigned to a 3 x 3 (feeder type x available space at the feeder) factorial arrangement among nine pens. Pens had one of three feeder types (concrete bunk, plastic, or wood barrel) and one of three amounts of available space in the feeder (0.33, 0.25, or 0.20 m animal(-1)). Total dry matter intake/pen, dry matter intake per animal, total weight gain/pen, daily weight gain/animal, and food waste were evaluated. Percentage of time spent at feeding and frequency of aggressive behaviors/12 h were recorded. We observed a higher total daily weight gain in ewes with a feeding space of 0.33 and 0.25 m animal(-1). The wastes were essentially insignificant for wood feeders in all feeding space treatments. The average number of aggressive behaviors was lower (P<-0.05) for animals kept in pens with feeding space of 0.33 m animal(-1) than for those maintained in pens with feeding space of 0.20 and 0.25 m animal(-1). Ewes with feeding space of 0.33 m animal(-1) fed simultaneously 54% of the time, while among pens with feeding spaces of 0.25 or 0.20 m animal(-1), this period was reduced to 41 and 30%, respectively. An available feeding space of 0.33 m animal(-1) is recommended for adult housed ewes, once it favors simultaneous access, lower competitive interactions at the feeder, and less variation in terms of individual weight gain among ewes.
Keywords: dominance relationship; ewes; feeding space; food waste